Membedah Anatomi Kejahatan Terorganisir: Studi Putusan Permufakatan Jahat di Era Digital - Kurniawan, Kurniawan; Mannan, Khaerul; Darwis, Muammad (Faculty of Law Andi Sapada Institute of Social Sciences and Business, 2024)
This study aims to analyze malicious consensus in narcotics cases in verdict number 101/Pid.Sus/2020/PN. Pre and the consideration of the panel of judges in imposing the sentence. Using normative research methods, this study examines legal norms, principles, theories, and legal arguments related to the case. The results of the analysis show that the defendant is legally and convincingly proven guilty of committing the crime of